2015
DOI: 10.1002/chem.201502970
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐Phase Combinatorial Synthesis and Biological Evaluation of Destruxin E Analogues

Abstract: The solid-phase combinatorial synthesis of cyclodepsipeptide destruxin E has been demonstrated. The combinatorial synthesis of cyclization precursors 8 was achieved by using a split and pool method on SynPhase Lanterns. The products were successfully macrolactonized in parallel in the solution phase by using 2-methyl-6-nitrobenzoic anhydride and 4-(dimethylamino)pyridine N-oxide to afford macrolactones 9, and the subsequent formation of an epoxide in the side chain gave 18 member destruxin E analogues 6. Biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…In these works, we successfully showed that the stereochemistry of the epoxide in the side chain plays an important role in inducing the morphological changes 11 and that a steric effect around the MeAla residue and replacement of Ile with Phe residue negatively affect the morphological change of OCLs. 12 Based on these SAR results, we also attempted the synthesis of molecular probes for target identification. An analogue possessing an alkyl azide moiety instead of an Ile residue induced morphological changes in OCLs; however, its biological activity was found to be 60-fold weaker than that of the natural product destruxin E (1e), indicating that further optimization is required for the preparation of an active molecular probe.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In these works, we successfully showed that the stereochemistry of the epoxide in the side chain plays an important role in inducing the morphological changes 11 and that a steric effect around the MeAla residue and replacement of Ile with Phe residue negatively affect the morphological change of OCLs. 12 Based on these SAR results, we also attempted the synthesis of molecular probes for target identification. An analogue possessing an alkyl azide moiety instead of an Ile residue induced morphological changes in OCLs; however, its biological activity was found to be 60-fold weaker than that of the natural product destruxin E (1e), indicating that further optimization is required for the preparation of an active molecular probe.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the other hand, acylproline 7a should be prepared in a stereoselective manner for scalable synthesis. Thus, we attempted Sharpless asymmetric dihydroxylation 43,44) of the terminal alkene in 14. Although stereoselectivity is known to be moderate in the asymmetric dihydroxylation of a terminal alkene, we found that reaction conditions in the presence of (DHQD) 2 PHAL favorably provided the desired diol 17 in a ratio of 17a : 17b = 86 : 14, whereas the reaction using an AD-mix β provided a diol in a ratio of 17a : 17b = 67 : 33.…”
Section: Scalable Synthesis Of Destruxin E (1) 41)mentioning
confidence: 99%
“…Despite the successful isolation of CDPs as naturally occurring secondary metabolites, chemical synthesis of CDP libraries leading to the discovery of de novo active CDPs remains a major challenge. In-solution macrolactonization methods had been developed for the chemical synthesis of natural CDPs (Figure a), , and some of these elegant methods have been applied to solid phase peptide synthesis (SPPS) to prepare certain types of CDPs, allowing for high-throughput affinity screenings, e.g., one-bead-one-compound libraries (Figure b). However, due to low efficiency of ester bond formation in SPPS, , the achievable level of crude quality and sequence complexity of CDPs are yet limited. To the best of our knowledge, such an approach only afforded a subtle improvement of the parental activity of natural CDPs. ,, Thus, such strategies using SPPS methods are yet insufficient to construct high diversity libraries to discover bioactive de novo CDPs.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, such an approach only afforded a subtle improvement of the parental activity of natural CDPs. 15,22,23 Thus, such strategies using SPPS methods are yet insufficient to construct high diversity libraries to discover bioactive de novo CDPs.…”
Section: ■ Introductionmentioning
confidence: 99%